2023
DOI: 10.2196/preprints.46590
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Involvement of Service Users and People With Lived Experience in Mental Health Care Innovation Through Design: Systematic Review (Preprint)

Abstract: BACKGROUND Mental health care faces challenges where innovation is seen as necessary. Many of these challenges require the involvement of service users and people with lived experience in developing and evaluating mental health care services. Since the development of digital interventions is becoming more prevalent, design approaches are also increasingly finding their way into mental health. There is evidence that these approaches can successfully integrate user experience into mental … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Phase of involvement was variable, with highest user involvement during the first stage of the co-production process, and only nine studies involving end users throughout all stages of co-production. The findings from this review overlap with the systematic review conducted by Veldmeijer et al, 31 who explored the extent to which stakeholders were involved in mental healthcare through design, including DMHIs. Both reviews found that the level of involvement of end users was lower in the latter phases.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Phase of involvement was variable, with highest user involvement during the first stage of the co-production process, and only nine studies involving end users throughout all stages of co-production. The findings from this review overlap with the systematic review conducted by Veldmeijer et al, 31 who explored the extent to which stakeholders were involved in mental healthcare through design, including DMHIs. Both reviews found that the level of involvement of end users was lower in the latter phases.…”
Section: Discussionmentioning
confidence: 56%
“…The review found most studies involved end users at a ‘co-thinker’ level within the matrix framework developed by Smits et al, 29 with no single study involving end users at the highest level as ‘decision maker’. These conclusions were supported by another review of 433 studies by Baines et al 31 who explored co-production within digital health innovation, implementation, and evaluation, and found whilst co-production is recognised as essential, it is rarely practised. Whilst these reviews concern co-production, they did not describe the methods and approaches to facilitate co-production, nor explore the barriers and added value to implementing co-production, which would be clinically useful for guiding decisions when co-producing DMHIs.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Existing models for sharing mental health experiences do have limitations. Many opportunities are offered only periodically by health services and educational institutions, such as those linked to service improvement [9] or health professional training [10]. Others require commitment to more formal positions, including the peer-support worker role in the UK [11], which may preclude access by those with existing commitments.…”
Section: Introductionmentioning
confidence: 99%